IMPLEMENTING SIGMUND FREUD’S PSYCHOANALYSIS THEORY IN THE ACADEMIC ARENA: A CRITICAL STUDY - Evita Yuliatul Wahidah; Yuminah Yuminah; Moh In'ami; Ulfa Ulfa (IMTIYAZ: Jurnal Ilmu Keislaman, 2022)
Sigmund Freud’s Psychoanalysis continuously develops as it also does in the academic arena. The theory explains humans’ personality structure which covers three aspects: id, ego, and superego. Freud has successfully developed a personality theory that divides the structure of the mind into three: consciousness, preconsciousness, and unconsciousness. From the above three, consciousness can be said to be the most dominant and important to determine humans’ behavior (analogy with an iceberg). In the academic arena, psychoanalysis has correlations that are complex and modificative. How far the implementation of psychoanalysis in the academic arena can be served as the main discussion of this article, which will be initiated on the theory in-depth and its critical analysis.Keywords: implementation, psychoanalysis, Sigmund Freud, education